Differences in situational power performance between playing positions in top level handball - Foretić,Nikola (2021)
ABSTRACT This study aimed to determine the differences in situational power performance between playing positions in handball. The following variables were analyzed: body height and weight, fastest shot, fastest sprint, highest jump, and average game time. The study sample comprised 412 handball players who participated at European championships. Backcourt players had the fastest shots and wing players presented the slowest shots among all playing positions. Wing players presented the fastest sprinting (29.09 km/h). Jumping performance showed the most diversity between the playing positions, and backcourt players jumped significantly higher than other players (16.76 cm).